2017
DOI: 10.1111/j.1936-704x.2017.03246.x
|View full text |Cite
|
Sign up to set email alerts
|

Design and Manufacturing of High Surface Area 3D‐Printed Media for Moving Bed Bioreactors for Wastewater Treatment

Abstract: Abstract:The specific surface area and topology of a biofilter media carrier is one of the most important parameters that determines the performance and efficiency of the system. In this work, mathematical models and 3D printing technologies were used to design and fabricate complex media designs that provide high specific surface area and refugia to protect biofilm from premature sloughing. Several gyroid based designs were proposed with specific surface area well beyond 2300 m 2 /m 3 . However, wall thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…The specific surface area and topology of the carrier determine the performance and efficiency of the system. Elliott et al designed and tested media carriers with sheet‐network Gyroid topologies. Their results indicate that the 3D‐printed Gyroidal media can withstand the prevalent conditions in moving bed bioreactors and that the NH 3 removal rate of the Gyroidal media is comparable to that of commercially available media.…”
Section: Applicationsmentioning
confidence: 99%
“…The specific surface area and topology of the carrier determine the performance and efficiency of the system. Elliott et al designed and tested media carriers with sheet‐network Gyroid topologies. Their results indicate that the 3D‐printed Gyroidal media can withstand the prevalent conditions in moving bed bioreactors and that the NH 3 removal rate of the Gyroidal media is comparable to that of commercially available media.…”
Section: Applicationsmentioning
confidence: 99%
“…These studies included, surface roughness measurement and modeling (Boschetto et al, 2013;Turner and Gold, 2015), dimensional accuracy (Ramli et al, 2018), surface roughness and quality (Agarwal et al, 2018;Armillotta, 2006). In contrast, given their high cost and complexity, only a few studies addressed MJ dimensional accuracy and surface roughness (Elliott et al, 2017;Khoshkhoo et al, 2018). Similarly, there has been a lack of extensive evaluation of such parameters for SLA (Campanelli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In conventional manufacturing technologies, it is known that dimensional accuracy and surface roughness are important properties to be continuously measured and improved for final products, particularly for applications involving small critical features (Elliott et al, 2017;Withell et al, 2011). Hence, there is even a more urgent need for dimensional capability comparison of the available 3DP technologies to guide future users about their limitations and process windows to further facilitate the applicability of these technologies and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [ 2 ] used stereolithography technology (SLA) to fabricate a semi-suspended spindle-shaped biocarrier with synthetic material (isocyanate and polyhydric alcohols), which demonstrated the effects of shaped microhabitats on biofilm growth and microbial community diversity [ 2 ]. In preliminary work on the topic, Elliott et al [ 27 ] demonstrated the manufacture of 3D-printed gyroid-based biocarriers using material jetting technologies and established the feasibility of implementing such technology for nitrification MBBRs [ 27 ].…”
Section: Introductionmentioning
confidence: 99%